2012
DOI: 10.1258/vasc.2012.cr0279
|View full text |Cite
|
Sign up to set email alerts
|

Limb salvage in a child with severely injured mangled lower extremity and muscle rigor

Abstract: Most surgeons make their decision to amputate or perform limb salvage of a mangled extremity based on scoring systems and grading of acute ischemic limb. We report on a child in whom limb salvage was achieved in spite of a clinical picture of irreversible ischemia with high mangled severity scores. Attempts to revascularize the mangled extremity of children are recommended, regardless of their severity scores and condition of the foot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There is a lot of controversy in literature about the use of this scale. Elsharawy et al [ 12 ] in his prospective study considered 46 upper and lower extremities and described, considering MESS injuries scoring higher than 7 and only secondary amputation, a MESS score specificity of 27.5 %. Menakuru [ 13 ] in his study confirmed the results obtained by Elsharawy et al He was able to save the limb in 20 (69 %) of 29 patients with MESS higher than 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lot of controversy in literature about the use of this scale. Elsharawy et al [ 12 ] in his prospective study considered 46 upper and lower extremities and described, considering MESS injuries scoring higher than 7 and only secondary amputation, a MESS score specificity of 27.5 %. Menakuru [ 13 ] in his study confirmed the results obtained by Elsharawy et al He was able to save the limb in 20 (69 %) of 29 patients with MESS higher than 7.…”
Section: Resultsmentioning
confidence: 99%
“…In Authors opinion it is better, at first time, to try limb salvage in children also in presence of high severity score. Elsharawy et al [ 12 ] described a case of limb salvage in a child with clinical picture of irreversible ischemia and high mangled severity scores. They recommended trying to revascularize and to save the limb in children, regardless clinical condition and severity scores.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction is the first consideration if the patient is young: high rates of limb salvage and function can be expected in pediatric patients, 11 therefore reconstruction is indicated even in severe injury. 12,13 Reconstruction is also favored in adults if plantar sensation is intact. 13,14 Bosse et al showed that patients may regain plantar sensation after reconstruction despite lack of sensation at the time of surgery, 15 which suggests that reconstruction may also be attempted in patients who have the possibility of regaining sensation, i.e., those with likely neuropraxia rather than avulsion or complete transection of the nerve.…”
Section: Situations In Which Reconstruction Is Favoredmentioning
confidence: 99%
“…1 summarizes injury characteristics that surgeons must assess and consider in making their decision to reconstruct. [12][13][14][15][16][17][18][19][20] In lower extremity trauma reconstruction, the surgeon must consider all options on the reconstructive ladder, or more recently elevator, to provide the patient with optimum function. 13,21 However, the lower rungs of the ladder, such as primary closure or skin grafting, are often inadequate in the setting of lower extremity trauma due to vast tissue deficits and Fig.…”
Section: Situations In Which Reconstruction Is Favoredmentioning
confidence: 99%
See 1 more Smart Citation